2020
DOI: 10.21203/rs.3.rs-25612/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

First detection of African swine fever (ASF) virus genotype X and serogroup 7 in symptomatic pigs in the Democratic Republic of Congo

Abstract: Background African swine fever (ASF) is a highly contagious and severe hemorrhagic viral disease of domestic pigs. The analysis of variable regions of African swine fever virus (ASFV) genome led to more genotypic and serotypic information about circulating isolates. The present study aimed at investigating the genetic diversity of ASFV strains in symptomatic pigs in South Kivu province of the Democratic Republic of Congo (DRC). Materials and Methods Blood samples collected from 391 ASF symptomatic domestic p… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 34 publications
(61 reference statements)
1
2
0
Order By: Relevance
“…However, after the reaction conditions were optimized, the two reaction systems showed the same detection sensitivity with different reaction temperatures. The detection limit for both the fluoresceinand biotin-labeled CRISPR/Cas12a reaction systems in this study was 6.8 copies per microliter, which is approach to the detection limits (sensitivities) of 6 copies per microliter as reported previously (27,32). This result suggests that the detection sensitivity of RPA-assisted RT-qPCR was higher than that of LAMP-assisted CRISPR/Cas12a.…”
Section: Discussionsupporting
confidence: 83%
See 2 more Smart Citations
“…However, after the reaction conditions were optimized, the two reaction systems showed the same detection sensitivity with different reaction temperatures. The detection limit for both the fluoresceinand biotin-labeled CRISPR/Cas12a reaction systems in this study was 6.8 copies per microliter, which is approach to the detection limits (sensitivities) of 6 copies per microliter as reported previously (27,32). This result suggests that the detection sensitivity of RPA-assisted RT-qPCR was higher than that of LAMP-assisted CRISPR/Cas12a.…”
Section: Discussionsupporting
confidence: 83%
“…For example, some researchers have used the CRISPR/Cas12a system combined with RPA isothermal amplification technology to detect human papillomavirus (HPV) and encephalitis B virus, which has simplified the detection process and shortened the detection time, while greatly improving detection accuracy (25,26). Several studies have reported the molecular detection techniques for ASFV, including RPA (27)(28)(29), RPA combined with RT qPCR (30), RPA combined with CRISPR/Cas (31), and LAMP combined with CRISPR/Cas12a (32). Some of them only use a single RPA or LAMP amplification technique to establish detection, while others establish joint methods with RT-qPCR or CRISPR/Cas, but these joint methods also only use fluorescence staining or colorimetric analysis without using test strip staining.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation